Edible coating as a factor of preserving freshness and increasing biological value of gingerbread cakes - Shulga, Oksana; Chorna, Anastasia; Arsenieva, Larisa; Gol, Artem (My University, 2016)
The article presents experimental study on the feasibility of using edible film (coating) as a means of preventing and cherstvenie method of increasing the biological value of gingerbread products. Grounded components of edible coating. Based on the organoleptic and physico-chemical parameters (moisture content, and namochuvanist kryhkuvatist) proved the feasibility and necessity of using edible coating, which also can increase the biological value of products as part of the coverage of linseed oil.
Keywords: їстівне покриття; пряникові вироби; біологічна цінність; строк зберігання; сьедобное покрытие; пряничные изделия; биологическая ценность; срок хранения; edible coating; gingerbread; biological value; shelf life; кафедра експертизи харчових продуктів